Overexpression of a Pak Choi Gene, BcAS2, Causes Leaf Curvature in Arabidopsis thaliana - Lin, Ye (Genes (Basel), 2021)
The LBD (Lateral Organ Boundaries Domain) family are a new group of plant-specific genes, which encode a class of transcription factors containing conserved Lateral Organization Boundary (LOB) domains, and play an important role in regulating the adaxial–abaxial polarity of plant leaves. In Arabidopsis thaliana, ASYMMETRIC LEAVES 2 (AS2) has a typical LOB domain and is involved in determining the adaxial cell fate. In this study, we isolated the BcAS2 gene from the pak choi cultivar “NHCC001”, and analyzed its expression pattern. The results showed that the BcAS2 encoded a protein made up of 202 amino acid residues which were located in the nucleus and cytomembrane. The Yeast two-hybrid system (Y2H) assay indicated that BcAS2 interacts with BcAS1-1 and BcAS1-2 (the homologous genes of AS1 gene in pak choi). In the transgenic Arabidopsis thaliana that overexpressed BcAS2 gene, it presented an abnormal phenotype with a curly shape. Taken together, our findings not only validate the function of BcAS2 in leaf development in Arabidopsis thaliana, but also contribute in unravelling the molecular regulatory mechanism of BcAS2, which fulfills a special role by forming complexes with BcAS1-1/2 in the establishment of the adaxial–abaxial polarity of the lateral organs in pak choi.